LEGAL PROTECTION OF THE RIGHTS OF LESBIAN WOMEN IN INDONESIA: A CRITICAL ANALYSIS OF STRUCTURAL DISCRIMINATION, SOCIAL NORMS AND THE HUMAN RIGHTS FRAMEWORK - Gunawan Widjaja (Adisam Publisher, 2026)
This study aims to critically analyse legal protection for the rights of lesbian women in Indonesia, focusing on three main dimensions: structural discrimination within the legal system and public policy; the role of heteronormative social norms in producing stigma and marginalisation; and the implementation gap between national and international human rights frameworks. The study employs a qualitative research method using a literature review approach. The research findings indicate that legal protection for lesbian women is in a paradoxical state: on the one hand, the 1945 Constitution, Law No. 39 of 1999 on Human Rights, CEDAW, and the ICCPR provide a strong normative foundation for non-discrimination; on the other hand, the absence of explicit recognition of sexual orientation as a protected category in secondary legislation creates interpretative loopholes that permit systematic discrimination in the spheres of education, employment, healthcare, and the judicial system. Heteronormative social norms reproduced through the institutions of the family, religion, and the mass media reinforce this structural discrimination, producing chronic minority stress and structural invisibility for lesbian women. This study concludes that effective protection requires a holistic approach encompassing the enactment of inclusive anti-discrimination legislation, the revision of the new Criminal Code to prevent the criminalisation of consensual same-sex relationships, the institutional transformation of public bureaucracy, and public education to deconstruct heteronormative norms. Without synergy between legal reform, social transformation, and consistent political commitment, the constitutional promise of equality before the law will remain empty rhetoric for lesbian women in Indonesia.